2018
DOI: 10.1080/15226514.2018.1460312
|View full text |Cite
|
Sign up to set email alerts
|

Physiology and selected genes expression under cadmium stress in Arundo donax L

Abstract: The effects of cadmium stress (0, 25, 50, 75, and 100 mg/L) on morpho-physiological features and selected genes (carotenoid hydroxilase, amidase, GR, bHLH, NRAMP and YSL) expression were demonstrated in Arundo donax L. The plants were assessed for Cd uptake and its effects on chlorophyll and antioxidants after 30 days of exposure. The expression of genes conferring metal tolerance was evaluated after 10 days of Cd exposure. The results showed a maximum Cd uptake in roots (872 mg/kg) followed by stem (734 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…This may be explained by the effective antioxidative defence in these plants and that Cd treatment was applied at a one-month-old stage of development. Similar resistance has also been found in the biomass plants Arundo donax [ 87 ].…”
Section: Discussionsupporting
confidence: 80%
“…This may be explained by the effective antioxidative defence in these plants and that Cd treatment was applied at a one-month-old stage of development. Similar resistance has also been found in the biomass plants Arundo donax [ 87 ].…”
Section: Discussionsupporting
confidence: 80%
“…Similarly, Czajka et al [20] reported an increase of NRAMP in Populus tremuloides leaf tissues caused by potassium nitrate groups rather than Ni. An increase in NRAMP expression has been studied in response to Cd stress [21]. But NRAMP genes can be overexpressed when Fe is deficient [22].…”
Section: Resultsmentioning
confidence: 99%
“…However, the transcriptional response of A. donax subjected to cadmium treatments is still incomplete and the molecular mechanism of cadmium stress on giant reed metabolic processes remains poorly understood. Recently, Shaheen et al [ 33 ] evaluated the effects of increasing concentrations of cadmium on the expression of selected genes (carotenoid hydroxylase, amidase, glutathione reductase, bHLH, NRAMP and YSL) in Arundo donax L. cultivated in hydroponic solution. The highest expression for these genes was observed in plants exposed to the highest Cd concentration (100 mg/L).…”
Section: Introductionmentioning
confidence: 99%
“…The highest expression for these genes was observed in plants exposed to the highest Cd concentration (100 mg/L). Moreover, the activity of several enzymes involved in the ROS scavenging (SOD, CAT, POD) was also measured revealing their activation at the highest cadmium concentration and confirming the onset of a secondary oxidative stress [ 33 ]. A study conducted in cohorts of A. donax strongly suggests that phytochelatin encoding genes ( Ad PCS1, Ad PCS2, and Ad PCS3) most likely contribute to Cd detoxification in A. donax and the presence of multiple PCS isoforms seems to be advantageous both to provide higher general levels of phytochelatin biosynthesis and to increase flexibility in HM resistance [ 34 ].…”
Section: Introductionmentioning
confidence: 99%